TIAA-CREF. (B), Organizing around the customer - from managing assets to managing relationships - Rosenthal, Jean W., 1945-; Elias, Jaan; Sudhir, K.; Podolny, Joel M. (Joel Marc) ([London] : SAGE, 2016)
By the end of his first year as CEO, President and Chairman, Herb Allison had initiated a transformation at TIAA-CREF (Teachers Insurance and Annuity Association-College Retirement Equities Fund). This case examines the self-evaluation process which allowed the company to review its relationships with its customers and redefine its goals and its culture.
Originally Published in: Rosenthal, J.W., Elias, J., Sudhir, K., & Podolny, J. (2006). TIAA-CREF (B): Organizing around the Customer: From Managing Assets to Managing Relationships. 06-019. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Teachers Insurance and Annuity Association; Financial services industry -- Management -- Case studies; Customer relations -- Management -- Case studies; Customer services -- Case studies